Endodontic flare-up incidence in pulp necrosis in Universitas Airlangga Dental Hospital (RSKGMP Universitas Airlangga) - Galih Sampoerno; Nanik Zubaidah; Wanda Salsabilla (Conservative Dentistry Journal, 2022)
Background : Dental caries occurs as a result of demineralization of the hard tissues of the teeth followed by the destruction of the organic matter, resulting in bacterial invasion and death of the pulp which can lead to pulp necrosis. One of the treatments for pulp necrosis is endodontic treatment. Endodontic treatment includes root canal preparation techniques, root canal irrigation materials, root canal dressing materials, and also root canal obturation techniques. In endodontic treatment can experience flare-ups. An endodontic flare-up is a pain or swelling after endodontic treatment that occurs in a relatively short time. Purpose : To describe the incidence of endodontic flare-ups in pulp necrosis at RSMKGP Universitas Airlangga. Methods : Conducted descriptive observasional research on patients who had endodontic treatment at UPF Dental Conservation, Dental and Oral Hospital, Faculty of Dental Medicine, Airlangga University in 2018, 2019, and 2020. Results : A total of 28 patients (30,1%) from 93 patients were experience pain or flare-ups after root canal treatment. Conclusion : From the result of this study, it can be concluded that there is still an incidence of endodontic flare-ups in pulp necrosis at RSKGMP Universitas Airlangga which is 30,1%.